Adolescence and the ontogeny of the hormonal stress response in male and female rats and mice. (November 2016) - Romeo, Russell D.; Patel, Ravenna; Pham, Laurie; So, Veronica M.
Highlights: Adolescence is associated with many neuroendocrine changes. Adolescents show stress-induced changes in ACTH and corticosterone secretion. These changes are dependent on stressor type, experience, and sex. Abstract: Adolescent development is marked by many changes in neuroendocrine function, resulting in both immediate and long-term influences on an individual's physiology and behavior. Stress-induced hormonal responses are one such change, with adolescent animals often showing different patterns of hormonal reactivity following a stressor compared with adults. This review will describe the unique ways in which adolescent animals respond to a variety of stressors and how these adolescent-related changes in hormonal responsiveness can be further modified by the sex and previous experience of the individual. Potential central and peripheral mechanisms that contribute to these developmental shifts in stress reactivity are also discussed. Finally, the short- and long-term programming effects of chronic stress exposure during adolescence on later adult hormonal responsiveness are also examined. Though far from a clear understanding of the neurobehavioral consequences of these adolescent-related shifts in stress reactivity, continued study of developmental changes in stress-induced hormonal responses may shed light on the increased vulnerability to physical and psychological dysfunctions that often accompany a stressful adolescence.